Experience with the sandwich technique in endovascular thoracoabdominal aortic aneurysm repair - Schwierz, Elisabeth; Kolvenbach, Ralf R.; Yoshida, Ricardo [UNESP]; Yoshida, Winston Bonetti [UNESP]; Alpaslan, Alper; Karmeli, Ron (Elsevier B.V., 2014)
Background: The sandwich technique is an endovascular off-the-shelf solution for patients with thoracoabdominal aortic aneurysms (TAAAs). In a sandwich configuration, the chimney stent runs in the middle of a space created by two or three aortic endografts.Methods: All patients with TAAAs who were treated with the sandwich technique were included in the study. Self-expanding Viabahn grafts (W. L. Gore and Associates Inc, Flagstaff, Ariz) were used as parallel grafts in the renal arteries and visceral vessels. Caudad-facing chimney grafts were used for the visceral arteries and cephalad-facing periscope grafts for the renal arteries.Results: During the study period, 32 patients with TAAAs were treated with sandwich grafts. Indication for the procedure in 43% was an acute onset of symptoms, including two patients with a rupture and a retroperitoneal hematoma. Three patients required an additional debranching procedure. A total of 104 chimney grafts were implanted. Two patients died postoperatively because of the operation. Major adverse events were recorded in five patients, including one patient with persistent paraplegia and two with permanent renal failure requiring dialysis. The incidence of chimney graft occlusion was higher in patients with three or four parallel grafts than in those with two chimney grafts only. Patients with chronic dissections had a 12-times higher incidence of chimney graft occlusion than aneurysm patients. The number of patients with type I or III endoleaks was higher in the group with three or four parallel grafts.Conclusions: The sandwich technique is an off-the-shelf endovascular alternative to treat patients with TAAAs in an emergent setting. The combination of chimney grafts with a periscope configuration enables a rapid endovascular aneurysm exclusion with acceptable midterm results.